2004
DOI: 10.1152/japplphysiol.00435.2003
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory change in preejection period: a new method to predict fluid responsiveness

Abstract: The accuracy and clinical utility of preload indexes as bedside indicators of fluid responsiveness in patients after cardiac surgery is controversial. This study evaluates whether respiratory changes (Delta) in the preejection period (PEP; DeltaPEP) predict fluid responsiveness in mechanically ventilated patients. Sixteen postcoronary artery bypass surgery patients, deeply sedated under mechanical ventilation, were enrolled. PEP was defined as the time interval between the beginning of the Q wave on the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 33 publications
4
47
2
3
Order By: Relevance
“…Although the power of the study was low, the preliminary results showed significant relationships between the ISTI and the cardiac output at any moment during the fluid No significant or systematic relationships between PTT and CO or ΔPTT and ΔCO were found. This is in contrast with earlier reports [8,9]. Probably, this absence originates from the limited power of this study to detect significances.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the power of the study was low, the preliminary results showed significant relationships between the ISTI and the cardiac output at any moment during the fluid No significant or systematic relationships between PTT and CO or ΔPTT and ΔCO were found. This is in contrast with earlier reports [8,9]. Probably, this absence originates from the limited power of this study to detect significances.…”
Section: Discussioncontrasting
confidence: 99%
“…The Initial Systolic Time Interval (ISTI) is defined as the period of time between those R-and C-points. The PTT was obtained by simultaneous ECG recording and arterial pressure wave tracing (P a ) obtained from the radial artery, in concordance with Bendjelid et al [8] and Feissel et al [9]. Both signals are commonly monitored in critically ill patients.…”
Section: Icg and Ecg Signal Registrationmentioning
confidence: 73%
See 1 more Smart Citation
“…Bu amaçla günümüzde değişik dinamik parametreler kullanılmakta olup, bunlardan biri PPV'dir (Şekil 2). PPV ile yapılan birçok çalışmada volüm replasmanına yanıt veren hastalarla, vermeyen hastaların ayırt edilmesinde yararlı olduğu gösterilmiştir (73)(74)(75) . Daha önce yapılan çalışmalarda PPV, arter trasesinin izlendiği monitörden alınan arter trasesi dokümünden manuel olarak hesaplanıyordu veya spesifik kardiyak debi monitörleri olan PiCCO, LiDCO gibi cihazlarla ölçülmekteydi.…”
Section: Basınç-volüm Ilişkisiunclassified
“…Geçen birkaç yıl da bu parametrelerin dışında başka parametrelerle de sıvı tedavisinin yönlendirilmesine çalışılmıştır. Bunlar arasında vena kava çapı değişikliği (74,82) , solunumla aortik akım değişikliği (83) , ejeksiyon öncesi süre değişiklik-leri (73,75) ve subkütan doku parsiyel oksijen basıncının (PscO 2 ) izlenmesidir (84) .…”
Section: Lidco (Lithium Dilution Cardiac Output)unclassified